Analisis Keuntungan Industri Rumah Tangga Susu Kedelai Di Kelurahan Taas Kecamatan Tikala Kota Manado - Datuan, Regina Noventia Putri; Maweikere, Audrey Maria; Rengkung, Leonardus Ricky (AGRI-SOSIOEKONOMI, 2024)
This study aims to analyze the benefits of soy milk in Taas Village, Tikala District, Manado City in March 2023. This research lasted for 3 months, from February 2023 to May 2023. The data used are primary data obtained using interview techniques. directly to soy milk business owners by using a list of questions as an aid in data collection, and secondary data obtained from literature studies in the form of literature, written sources or documents that are relevant to this research. Based on profit data for the processed soy milk home industry, this soy milk business incurs a total cost in a month or 26 working days of IDR 11,170,279 and an average of IDR 429,626 per day. The total revenue is IDR 23,400,000 with an average revenue divided by 26 working days, which is IDR 900,000 per day or 20 bottles of soy milk, and earns a profit of IDR 12,229,721 with an average profit for 3 (three) businesses of IDR 470,374. This shows that the soy milk home industry business in the Taas Village is feasible to maintain and develop.